Multidimensional assessment of strongly irregular voices such as in substitution voicing and spasmodic dysphonia: A compilation of own research. (April 2015) - Moerman, Mieke; Martens, Jean-Pierre; Dejonckere, Philippe
Abstract: This article is a compilation of own research performed during the European COoperation in Science and Technology (COST) action 2103: 'Advance Voice Function Assessment', an initiative of voice and speech processing teams consisting of physicists, engineers, and clinicians. This manuscript concerns analyzing largely irregular voicing types, namely substitution voicing (SV) and adductor spasmodic dysphonia (AdSD). A specific perceptual rating scale (IINFVo) was developed, and the Auditory Model Based Pitch Extractor (AMPEX), a piece of software that automatically analyses running speech and generates pitch values in background noise, was applied. The IINFVo perceptual rating scale has been shown to be useful in evaluating SV. The analysis of strongly irregular voices stimulated a modification of the European Laryngological Society's assessment protocol which was originally designed for the common types of (less severe) dysphonia. Acoustic analysis with AMPEX demonstrates that the most informative features are, for SV, the voicing-related acoustic features and, for AdSD, the perturbation measures. Poor correlations between self-assessment and acoustic and perceptual dimensions in the assessment of highly irregular voices argue for a multidimensional approach.